Defining, conceptualising and operationalising community empowerment: a scoping review protocol. Issue 5 (3rd May 2022) - Babatunde, Gbotemi Bukola; Schmidt, B; Gwelo, Netsai Bianca; Akintola, Olagoke
Abstract : Introduction: Community empowerment is a core concept in health promotion theory and practice. Several authors have defined and conceptualised the term differently. However, we did not find any synthesis of the various definitions of, and meanings attached to, community empowerment and the various conceptualisations, operationalisations, and the indicators for measuring community empowerment in the health promotion literature. The aim of this scoping review is to characterise and synthesise various definitions, conceptualisations, operationalisations and indicators for measuring community empowerment in the literature. Methods and analysis: This scoping review will follow scoping review methods outlined by Arksey and O'Malley. We will identify relevant studies from 1986 onwards, written in any language, conducted anywhere in the world, and published in PubMed, PsycINFO, CINAHL, Web of Science and Medline. Two reviewers will independently screen titles, abstracts and full-text articles, after which they will carry out data extraction and analysis. We will develop a numerical and narrative synthesis of the definitions, conceptualisations, operationalisations and measurements of community empowerment in relation to health promotion and/health outcomes. Ethics and dissemination: This scoping review does not require ethics approval, as we will only include information from previously conducted studies and we will not involve human participants.